Improving maternal oral health knowledge and practices: an intervention from Sri Lanka - Surani Fernando (Journal of Research in Medical and Dental Science, 2015)
Background: Oral health is one of the most common chronic diseases among school children in Sri Lanka. However, there is little or no priority given for oral health preventive strategies. The role of mother or the primary carer of children was identified as significant in oral health promotion. In this context it was vital to empower mothers or care givers of preschool children to improve oral health of children.